Relationship of Participative planning, Planning Alignment and Regional Development Performance: Evidence from Special Region of Yogyakarta - Andilo Toham; Ernan Rustiadi; Bambang Juanda; Rilus Kinseng (Universitas Muhammadiyah Sidoarjo, 2021)
Participatory planning is a necessity. Unfortunately, participatory planning has various problems that make it ineffective. Human resource capacity as an input factor for participatory planning is still inadequate. The participatory planning process has not optimized the best way of producing the outputs that are needed by the community. Spatial aspects of planning, activities in the space, and budgeting must be aligned. However, empirical facts show the inconsistency of development planning. The purpose of this study is to analyze the relationship between community participation in planning and regional development performance through spatial planning, development, and budget planning alignment, as the mediating variable. This study explore measurement of all three variables using quantitative indicators. The results of this study, using SEM PLS, indicate that the direct relationship of community participation and the performance of infrastructure development is significant if it does not include the mediation variable. Process, results of participatory planning, alignment of spatial and development plans, and alignment of strategic plans with work plans are significant variables. Therefore, local governments need to make efforts to improve participation processes in spatial planning and development so as to improve the regional development planning alignment and performance